Educational administration and its role in the success of the educational process (Journal of the College of Basic Education, 2022)
The importance of educational administration comes as one of the important foundations in improving and developing the educational process. The concept of classroom educational administration is no longer the same as it was before Today, it includes many trends that concern the educational process, including students, faculty members, curricula and teaching methods, in addition to regulating relations between the school and the local community. Providing the appropriate conditions and capabilities that help achieve the goals and the philosophy of education and administration. The research includes the concept of educational management and the principles on which it is based, from planning, organizing and directing, then talking about the types of educational administration, then human relations in educational administration and its concept in Islam, and finally what are the most important problems facing educational administration.